CULTURE OF THE COMMUNITY IN KEEPING THE ENVIRONMENT AROUND THE MARKET MANDAU KELURAHAN DURI TIMUR KECAMATAN MANDAU KABUPATEN BENGKALIS - SEPTIANA, SEPTIANA; Drs. Dasrizal, MP, Drs. Dasrizal, MP; Zuriyani, M.Si, Elvi (Pendidikan Geografi, 2014)
ABSTRACTÂ Creating a clean and healthy environment is a shared responsibility, especially people that are around the environment. Communities have an important role in keeping the environment as well as creating a culture of a clean and healthy environment. This study aims to obtain, information, and an overview of Public Culture In Maintaining Environmental Cleanliness around the Village Market Saber Saber Duri subdistrict East Bengkalis views of: : 1) the habit of taking out the trash, 2) the habit of cleaning up the environment, 3) infrastructure utilization habits.This research method is descriptive. Descriptive research is intended to make plans about situations or events that are interconnected. The location of this research is in the East Village District of Saber Duri Bengkalis, this area of research is in RW I, RW II, III RW, RW IV. Sampling was done with the method: proportional random sampling, 15% of 631 people as many as 96 respondents.Based on the research results, it can be concluded as follows: 1. In view of the habit of taking out the trash is still much to throw it on the curb is equal to 46.9%, people still use plastic as trash, as well as the lack of public attention to the cleanliness of their neighborhood, 2. In view of the habits of the community in cleaning up the environment in general public only occasionally keeping the environment 52%, and also rarely made public mutual cooperation, to contribute, even meeting the environmental hygiene, so that the people themselves have not been keeping the environment in which they live well, 3.Di view of habits in the use of infrastructure in general hygiene sometimes people just trash properly utilize 53.1%, when the government already provides a means garbage and janitor.Â